SISTEM PAKAR IDENTIFIKASI PENYAKIT KUCING MENGGUNAKAN METODE FORWARD CHAINING BERBASIS ANDROID - Wardana, Anggit Prima; Destiawati, Fitriana; Andrari, Finata Rastic (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Many cats are kept by Indonesians. However, they are unable to adequately care for them, hence a tool that can identify and explain cat ailments is required. Making applications that make use of expert systems based on Android can do this. Forward chaining will be the research technique employed in this application to build the system. This Android software aids in the diagnosis of illnesses in cats. Additionally, expert system applications can make use of the forward chaining strategy.